Aortic Cross-Sectional Area/Height Ratio and Outcomes in Patients With Bicuspid Aortic Valve and a Dilated Ascending Aorta. (June 2017) - Masri, Ahmad; Kalahasti, Vidyasagar; Svensson, Lars G.; Alashi, Alaa; Schoenhagen, Paul; Roselli, Eric E.; Johnston, Douglas R.; Rodriguez, L. Leonardo; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background—: In patients with bicuspid aortic valve and dilated proximal ascending aorta, we sought to assess (1) factors associated with increased longer-term cardiovascular mortality and (2) incremental prognostic use of indexing aortic root to patient height. Methods and Results—: We studied 969 consecutive bicuspid aortic valve patients (50±13 years; 87% men) with proximal aorta ≥4 cm, who also had a gated contrast-enhanced thoracic computed tomography or magnetic resonance angiography. A ratio of ascending aortic area/height was calculated on tomography, and ≥10 cm 2 /m was considered abnormal, as previously reported. Society of Thoracic Surgeons score and cardiovascular death were recorded. Greater than or equal to III+ aortic regurgitation and severe aortic stenosis were seen in 37% and 10%, respectively. Society of Thoracic Surgeons score and right ventricular systolic pressure were 2±3 and 15±16 mm Hg, respectively. Abnormal ascending aortic area/height ratio was noted in 33%; 44% underwent ascending aortic surgery at 34 days. At 10.8 years (interquartile range, 9.6–12.3), 82 (9%) died (0.4% in-hospital postoperative mortality). On multivariable Cox survival analysis, ascending aortic area/height ratio (hazard ratio, 2; 95% confidence interval, 1.20–3.35) was associated with cardiovascular death, whereas aortic surgery (hazard ratio, 0.46; confidence interval, 0.26–0.80) was associated with improved survival (both P <0.01). Of the 405 patients with ascending aortic diameter of 4.5 to 5.5 cm, 64% had an abnormal ascending aortic area/height ratio, and 70% deaths occurred in patients with an abnormal ratio. Conclusions—: In bicuspid aortic valve patients with dilated proximal ascending aorta, ascending aortic area/height ratio was independently associated with cardiovascular death. Abstract : Supplemental Digital Content is available in the text.